Elisha Kent Kane (1820-1857) - Martin, Constance (ARCTIC, 1984)
The first American arctic explorer of note, Elisha Kent Kane was a man of broad interests and varied talents. Although he died when he was only 37 years old, he distinguished himself as a career naval officer, medical doctor, scientist, author, and artist, and his death inspired a funeral procession by train from New Orleans to the home of his birth in Philadelphia. . Well-travelled prior to his mid-century arctic voyages, Kane had journeyed through South America, Africa, Europe, and the Far East. Small of stature and physically frail as a result of a rheumatic heart, the naval doctor nevertheless sought challenges of physical endurance, which led to his volunteering for the arduous U.S. Polar Expedition in 1850 as ship's surgeon and again in 1853 as leader. . the serious search for a Northwest Passage had been a predominantly British enterprise. Not until President Zachary Taylor and Henry Grinnell, the wealthy New York shipbuilder, responded to Jane Franklin's appeal for aid in finding her missing husband and his crew did the United States officially enter into the exploration of the Arctic. . Motivated by humanitarian interests, Congress and Grinnell co-sponsored two searches. Politically, the undertaking allowed the United States to participate with Britain in exploration within the territory of North America. There was a further justification as well. U.S. Navy oceanographers were intrigued with the theory of an Open Polar Sea . The first voyage gave no evidence of an Open Polar Sea; Kane, undaunted, sought command of another. . The first voyage had attempted a passage through Lancaster Sound and north into Wellington Channel. The second, under Kane's leadership and including only one ship, sailed due north up the west coast of Greenland to latitude 78°N, where the Advance was icebound and never released. . By the spring of 1855, after three summers and two winters that proved far harsher and more impoverished than the men's most pessimistic fears, Kane and his crew faced imminent starvation. Consequent ...